Carvedilol use is associated with reduced cancer risk: A nationwide population-based cohort study. (1st April 2015) - Lin, Chin-Sheng; Lin, Wei-Shiang; Lin, Cheng-Li; Kao, Chia-Hung
Abstract: Background: To investigate the effect of carvedilol on the incidence of cancer in a large population-based cohort study. Methods: Data were obtained from the Taiwan National Health Insurance Research Database. The cohort study included 6771 patients who received long-term carvedilol treatment between 2000 and 2010 (carvedilol cohort) and 6771 matched controls (noncarvedilol cohort). A Cox proportional hazards model was used to evaluate the risk of cancer in the patients treated with carvedilol. Results: With the mean follow-up period of 5.17 years and 4.93 years in the carvedilol and noncarvedilol cohorts, respectively, the patients in the carvedilol cohort had a 26% reduction of cancer risk compared with those in the noncarvedilol cohort (hazard ratio [HR] = 0.74; 95% confidence interval [CI] = 0.63–0.87; p < .001). The sex-specific carvedilol to noncarvedilol relative risk was lower for both women (HR = 0.73; 95% CI = 0.56–0.94) and men (HR = 0.75; 95% CI = 0.61–0.92). Moreover, stratified by cancer site, treatment with carvedilol in the carvedilol cohort resulted in significantly lower incidence of stomach and lung cancers than in the noncarvedilol cohort. Conclusion: This nationwide population-based cohort study demonstrated that long-term treatment with carvedilol is associated with reduced upper gastrointestinal tract and lung cancer risk, indicating that carvedilol could be a potential agent in these cancers prevention. Highlights: To explore the effect of carvedilol on cancer incidence, the study included 6771 patients who received carvedilol treatment. The patients in the carvedilol cohort had a 26% reduction of cancer risk. Treatment with carvedilol resulted in significantly lower incidence of upper gastrointestinal tract and lung cancers.